Current practice and research directions in hydrodynamics for FLNG-side-by-side offloading. (15th June 2018) - Zhao, W.; Milne, I.A.; Efthymiou, M.; Wolgamot, H.A.; Draper, S.; Taylor, P.H.; Eatock Taylor, R.
Abstract: The offloading of LNG from a ship-shaped FLNG facility to a carrier in a side-by-side configuration in the open sea is a new operation in the offshore industry. Its novelty means that there is limited guidance available for potential FLNG operators when undertaking operability assessments. The criteria for design of side-by-side offloading operations at sea are reviewed, largely based on the pioneering work by Shell. Whilst many advances have been made, several areas of uncertainty remain, particularly associated with the underlying complex non-linear hydrodynamics. To this end, a review of the relevant hydrodynamics associated with side-by-side offloading is presented. Within this scope, the key factors that are likely to play an important role in determining side-by-side offloading operability include roll motions of LNG carriers, liquid cargo sloshing and free surface motions in the gap between vessels. Each of these phenomena can exhibit resonance, with the response amplitude of roll motions, sloshing and free surface motions in the gap being sensitive to damping levels and excitation frequencies. To explore the present understanding of the hydrodynamic excitation and damped response of these phenomena, recent developments have been reviewed and critiqued; these encompass numerical simulations, physical model tests and full scale measurements. Recommendations for future work directions to expand the current understanding and address shortcomings are also provided. Highlights: Recent developments of hydrodynamics associated with side-by-side offloading are reviewed. Key areas include roll motion/damping, sloshing and gap resonance. Numerical simulations, scaled model tests and full scale measurements are covered. Research opportunities have been identified and recommendations for future work are provided.